Joint signal carrier frequency and 2D DOA estimation method based on space-time processing - SUN Xiao-ying; CHEN Jian; LIN Lin (Tongxin xuebao)
A joint estimation method of frequency and 2D（two-dimensional） direction of arrival was proposed for arbitrary array. Spatial domain sampling and time domain sampling were used synchronously to construct space-time cross-correlation matrixes, and 2D-ESPRIT method was utilized to estimate the 2D parameters in this method. Without spectral peak searching and complex computation, and only needing three guiding sensors, the carrier frequency, azimuth and elevation angles of M independent sources could be estimated by using M sensors. The effectiveness of this method is demonstrated by some simulation examples.